Job quality of young graduates in southern European countries - Dias, Maria do Rosário Carvalho Marques (2019)
International policies related to employment and the education system have spread concern about job quality. This dissertation uses the European Union Labour Force Survey to explore the job quality of young bachelor and master graduates in Southern European Countries, namely Portugal, Greece and Italy. After analysing the characteristics of job quality, those were matched with the available information in the database. A fuzzy cluster analysis allowed to understand the different typologies prevailing in each country. The results achieved show that the young graduates (20 to 24 years old) prevail in the typology with the lowest income, involuntary contracts with flexible duration, part-time job and some atypical work, entering the labour market through these conditions and they are searching for another job. The young adult graduates (25 to 29 years old) prevail in a typology with moderate income, contract from seven months to unlimited duration, full-time and working regular hours. However, some graduates are assigned to stable jobs with long-term contract, full-time job working long hours, higher income and disturbances in work-life balance. Considering the distribution of the graduates by job quality, around a third of the sample is aligned with a single typology where slightly more than half has a combination of two. This shows that having a higher education is no longer sufficient to guarantee a high-quality job for all graduates. Policy-makers should take initiatives to encourage employers to foster job quality and allow young people to have a better transition to and trajectory in the labour market.